Revisiting the Ediacaran-Cambrian boundary in the Ossa-Morena Zone (SW Iberia) - Pereira, M. F. (2019)
Some of the best outcrops of Iberia to study the Ediacaran-Cambrian boundary are located in the Ossa- Morena Zone. In the Crato-Campo Maior region (SW Iberia, Portugal), this stratigraphic boundary is marked by an angular unconformity (Gonçalves, 1971). The Ediacaran sedimentary rocks of the Série Negra Group (maximum depositional age of c. 545 Ma; Linnemann et al., 2008) are overlain by Early Cambrian strata. A folded foliation has been recognized in the Ediacaran metagreywackes, metapelites, black metachert, marbles and metabasic rocks (Pereira & Silva, 2002). This deformation event is previous to the intrusion of c. 526-525 Ma granitic rocks (Barquete and Barreiros plutons; Pereira et al., 2011; Sánchez-García et al., 2013), and is not represented in the unconformable overlying Early Cambrian strata including sandstone (maximum depositional age of c. 532 Ma; Pereira et al., 2011). At the base of the lower Cambrian stratigraphic section there is the Freixo-Segóvia volcanosedimentary complex consisting of felsic tuff interbedded with conglo-merate and rhyolitic-dacitic lava flow (Pereira et al., 2006). The conglomerate is composed of pebbles of volcanic rock (basalt, rhyolite, dacite and mafic and felsic tuff), granitic rocks, chert, quartzite, arkosic sandstone, greywacke and shale in a tuffaceous sandy matrix. This volcano-sedimentary complex is overlain by a sequence of sandstone and shale passing vertically to limestone beds which have been attributed to the lower Cambrian (Pereira et al., 2006) (see Fig. 12). An ongoing research project intends to date the volcanic rocks of the volcano-sedimentary complex using U-Pb zircon geochronology. The absolute dates determined from these volcanic rocks will provide the time framework for the calibration of the existing stratigraphic scheme based on regional correlation.